Risk factors for upper limb fractures due to unintentional injuries among adolescents: a case control study from Sri Lanka - Hemali Jayasekera; Samitha Siritunga; Upul Senarath; Paramjit Gill (BMC, 2022)
Abstract Background Injuries are the number one cause for morbidity and mortality among adolescents. Adolescent fractures are a hidden public health problem in Sri Lanka. Upper limb fractures are common in adolescents due to various risk factors. Many injuries are predictable and can be prevented by identifying the risk factors. The aim of the study was to determine the risk factors for upper limb fractures among adolescents in Sri Lanka. Methods A case control study was undertaken with 450 cases and 450 controls. Cases were recruited consecutively from all major hospitals among the adolescent victims who had admitted with newly diagnosed upper limb fractures in the district of Colombo. Controls were apparently healthy adolescents from the same district and excluded who had previous upper limb fractures. The age and gender were not matched in selecting controls since these two factors were potential risk factors for adolescent fractures according to previous literature. Risk factors for upper limb fractures were assessed by odds ratio (OR) with 95% confidence interval (CI) and adjusted for possible confounding by performing logistic regression analysis. Results The mean age of the cases was 13.62 years with a Standard Deviation (SD) of 2.8 and controls was 12.75 years (SD = 2.7) respectively. Having a high standard of living index (OR = 3.52; 95%CI: 2.3-5.2, p < 0.001), being in a high social class category (social class I & II) (OR = 2.58, 95%CI: 1.7-3.92, p < 0.001), engage in physical or sports activity (OR = 9.36; 95%CI: 3.31-26.47, p < 0.001), watching television (OR = 1.95; 95%CI: 1.18 -3.22, p = 0.009), playing video or computer games (OR = 2.35; 95%CI: 1.7-3.24, p < 0.001), and attending extra classes (OR = 1.82; 95%CI: 1.2-2.7, p = 0.007) were risk factors for having a upper limb fracture. Risk factors for upper limb fractures following adjusted for confounders were siblings in the family (aOR = 11.62, 95% CI: 6.95-41.29, p = 0.03) and attend extra classes after school hours (aOR = 2.51, 95%CI: 0.68-0.93, p = 0.04). Two significant effect modifications between being a Buddhist and low standard of living index (p < 0.001) and having one sibling in the family and attend extra classes after school hours (p = 0.01) were observed. Conclusions Modifiable risk factors in relation to lifestyle factors and socioeconomic position were important determinants of upper limb fracture risk in adolescents. Many fractures can be prevented by strengthening awareness programmes in the community.